False Equivalence: Are Liberals and Conservatives in the United States Equally Biased?. (March 2019) - Baron, Jonathan; Jost, John T.
On the basis of a meta-analysis of 51 studies, Ditto et al. (this issue, p. 273) conclude that ideological bias is equivalent on the left and right of U.S. politics. In this commentary, we contend that this conclusion does not follow from the review and that Ditto and his colleagues are too quick to embrace a false equivalence between the liberal left and the conservative right. For one thing, the issues, procedures, and materials used in the studies reviewed by Ditto and his colleagues were selected for purposes other than the inspection of ideological asymmetries. Consequently, methodological choices made by researchers were systematically biased to avoid producing differences between liberals and conservatives. We also consider the broader implications of a normative analysis of judgment and decision making and demonstrate that the bias examined by Ditto and his colleagues is not, in fact, an irrational bias, and that it is incoherent to discuss bias in the absence of standards for assessing accuracy and consistency. Other conclusions about domain-general asymmetries in motivated social cognition have suggested that epistemic virtues are more prevalent among liberals than conservatives, and these conclusions are closer to the truth of the matter when it comes to current American politics. Finally, we question the notion that the research literature in psychology is necessarily characterized by liberal bias, as several authors have claimed.